Stress, coping and life satisfaction: a study among reserve officer training unit (PALAPES) and police undergraduate voluntary corps (SUKSIS) of Universiti Malaysia Sarawak - Nurhalida, Shoib (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Stress and coping are important variables that strongly related to each other and life satisfaction is the other element corresponds to both variables. This study examined the relationship between stress and coping strategies namely problem focused and emotion focused strategies and life satisfaction. 150 respondents were randomly selected from Kenanga college of University Malaysia Sarawak. Respondents completed a set of questionnaire of Perceived Stress Scale (PSS-10), Coping Strategies Inventory (CSI-32) and Satisfaction with Life Scale (SWLS). Result indicated that female experience more stress than male respondents. Stress has a significant relationship with problem focused strategies and this study recorded that there was no correlation between stress and life satisfaction. Multiple regression tests was carried out to test which coping strategies influenced life satisfaction and the result shows that students use emotion focused strategies as their ways of coping.